Outcomes of Patients Discharged From a First Episode Psychosis Service in Derby City and South County - Mahendra Kumar; Remon Mosaad (BJPsych Open, 2025)
Aims: The Early Intervention for Psychosis (EIP) service in Derby City and Derbyshire South County provides care for individuals aged 14–65 experiencing a first episode of psychosis. The service supports a diverse population across Derby City (Census 2021 population: 261,400) and Derbyshire South County (Census 2021 population: 349,000), reflecting varying demographic and clinical characteristics. This study examines diagnostic outcomes, referral sources, and discharge destinations of discharged patients.